1991
DOI: 10.1159/000138860
|View full text |Cite
|
Sign up to set email alerts
|

Cholinoceptor Blockers Protect against Ethanol-Induced Gastric Mucosal Damage in Rats

Abstract: The role of the cholinergic nervous system in ethanol-induced gastric mucosal damage has been examined in rats. Oral administration of 50 or 80% ethanol produced haemorrhagic lesions which were reduced by atropine pretreatment (0.65, 2.5, 5 or 10 mg/kg injected i.p.); there was lesser protection against the higher dose of ethanol. Pirenzepine (a specific M1 receptor antagonist) pretreatment (0.1, 0.2, 1 or 2 mg/kg, injected s.c.) produced a similar anti-ulcer effect. Hexamethonium administration (5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The atropine dose we used was similar to previous studies,25,26 and was half the dose reported to have a full blocking effect in studies of heart rate variability 27. Immobilization and gavage tended to be associated with longer emptying times, although significance was never reached in the breath test, possibly due to the relatively low number of animals studied, especially in the gavage group.…”
Section: Discussionmentioning
confidence: 70%
“…The atropine dose we used was similar to previous studies,25,26 and was half the dose reported to have a full blocking effect in studies of heart rate variability 27. Immobilization and gavage tended to be associated with longer emptying times, although significance was never reached in the breath test, possibly due to the relatively low number of animals studied, especially in the gavage group.…”
Section: Discussionmentioning
confidence: 70%
“…Even in cases with successful healing, the high relapse rate as well as other unexpected severe sideeffects (including mortality) after vagotomy suggest that it should not be recommended as a treatment of choice for gastric ulcers (Weinberg & McLenathen 1963;Stabile & Passaro 1983); antimuscarinic drugs have, therefore, been a more suitable alternative form of therapy. Atropine, an antimuscarinic drug, reduces the severity of gastric lesion formation (Foschi et a1 1986;Cho & Ogle 1991). However, contrasting results have been reported in another study using intragastric treatment with antisecretory doses of atropine (Martinotti et al 1984).…”
mentioning
confidence: 99%